Collaborating to Enhance Tolerance Among Bandung's Students of Diverse Religions - Wibisono, Muhammad Yusuf; Viktorahadi, Bhanu; Rahman, Mohammad Taufiq (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the perceptions of tolerance held by students at UIN Bandung and Parahyangan Catholic University (UNPAR), two religiously affiliated postsecondary educational establishments in Bandung. The data for this research was gathered through document reviews and interviews using a qualitative methodology. Fifty students from UIN Bandung and fifty from UNPAR Bandung were interviewed. This study discovers that students' perceptions of their religious texts—the Bible and the Qur'an—have an impact on how tolerant they are Socially, it is discovered that Indonesians' conception of tolerance has a national dimension based on the national ideology. Religious and social concepts provide these kids with the foundation for tolerance in a variety of ways. Students at UIN Bandung continue to exhibit tolerance, but only within the framework of their religion—Islam. On the other hand, tolerance is practiced in both the social and individual environments at UNPAR, a campus that is more diverse and cosmopolitan. Collaboration strengthens the two student groups' tolerant attitudes. This collaboration later initiated the birth of the Halaqah Damai (Circle of Peace) as a forum for the two student groups to have dialogue and understand the essence of religious tolerance to be disseminated in their respective environments.